Epigenetic DNA Modifications Are Correlated With B Chromosomes and Sex in the Cichlid Astatotilapia latifasciata - Cardoso, Adauto Lima; Fantinatti, Bruno Evaristo de Almeida; Venturelli, Natália Bortholazzi; Carmello, Bianca de Oliveira; Oliveira, Rogério Antonio de; Martins, Cesar (Frontiers in Genetics, 2019)
Supernumerary B chromosomes are dispensable elements found in several groups of eukaryotes, and their impacts in host organisms are not clear. The cichlid fish Astatotilapia latifasciata presents one or two large metacentric B chromosomes. These elements affect the transcription of several classes of RNAs. Here, we evaluated the epigenetic DNA modification status of B chromosomes using immunocytogenetics and assessed the impact of B chromosome presence on the global contents of 5-methylcytosine (5mC) and 5-hydroxymethylcytosine (5hmC) and the molecular mechanisms underlying these variations. We found that the B chromosome of A. latifasciata has an active pattern of DNA epimarks, and its presence promotes the loss of 5mC in gonads of females with B chromosome (FB+) and promotes the loss of 5hmC in the muscle of males with the B element (MB+). Based on the transcriptional quantification of DNA modification genes (dnmt, tet and tdg) and their candidate regulators (idh genes, microRNAs and long noncoding RNAs) and on RNA-protein interaction prediction, we suggest the occurrence of passive demethylation in gonads of FB+ and 5hmC loss by Tet inhibition or by 5hmC oxidation in MB+ muscle. We suggest that these results can also explain the previously reported variations in the transcription levels of several classes of RNA depending on B chromosome presence. The DNA modifications detected here are also influenced by sex. Although the correlation between B chromosomes and sex has been previously reported, it remains unexplained. The B chromosome of A. latifasciata seems to be active and impacts cell physiology in a very complex way, including at the epigenetic level.